2017
DOI: 10.3390/ma10070781
|View full text |Cite
|
Sign up to set email alerts
|

Creep Behavior of High-Strength Concrete Subjected to Elevated Temperatures

Abstract: Strain is generated in concrete subjected to elevated temperatures owing to the influence of factors such as thermal expansion and design load. Such strains resulting from elevated temperatures and load can significantly influence the stability of a structure during and after a fire. In addition, the lower the water-to-binder (W–B) ratio and the smaller the quantity of aggregates in high-strength concrete, the more likely it is for unstable strain to occur. Hence, in this study, the compressive strength, elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Under the unstressed conditions, due to the dehydration of the ettringite and the loss of physically bound water, there was a slight increase of porosity after the mortar was heated at 200 °C [ 7 , 30 ]. However, when heated at 400 °C and the temperature after that temperature, the porosity of mortar increases significantly.…”
Section: Test Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Under the unstressed conditions, due to the dehydration of the ettringite and the loss of physically bound water, there was a slight increase of porosity after the mortar was heated at 200 °C [ 7 , 30 ]. However, when heated at 400 °C and the temperature after that temperature, the porosity of mortar increases significantly.…”
Section: Test Resultsmentioning
confidence: 99%
“…Many factors lead to the decrease of compressive strength as concrete exposure to high temperature [ 7 ]. As we have known, the thermal expansion of cement paste and aggregate were different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that thermal shock damage can have serious adverse effects on the static performance parameters of granite [8,9]. It was proved that high-strength concrete would begin to crack when suffering from a temperature step frequently changing from 18 to 20 °C [10,11]. It was suggested that the different thermal expansion coefficients of the material components would lead to intergranular compression and tensile force, which might result in a specific microcrack network [12,13,14,15,16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%